Anticancer Efficacy of a Combination of Curcuma longa L. Rhizome and Annona muricata L. Leaf Extracts Against T47D Cells - Pebriani, Sonia Ardilla; Bhagawan, Weka Sidha; Prastiyanto, Muhammad Evy; Rukmana, Rizal Maarif; Pratiwi, Rarastoeti; Suhendi, Andi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Breast cancer remains one of the most prevalent malignancies worldwide. The use of combinations of natural products is increasingly recognized as a promising strategy for cancer treatment. Turmeric rhizome (Curcuma longa L.) and soursop leaves (Annona muricata L.) are two natural materials known for their anticancer potential. This study aimed to identify the phytochemical constituents of turmeric rhizome and soursop leaf extracts and to evaluate the anticancer activity of their combination against T47D breast cancer cells. Turmeric and soursop leaves were extracted with 96% ethanol using the maceration method. Raw material standardization was performed by measuring water content, ethanol-soluble content, and water-soluble content. The extract was standardized by thin-layer chromatography. T47D and Vero cell lines were used in this study. Compound identification was performed using Liquid Chromatography–Quadrupole Time-of-Flight Mass Spectrometry (LC/Q-TOF-MS). The candidate combination ratio was determined using the simplex lattice design approach in Design Expert 13 software. Cytotoxicity and antiproliferative effects were assessed using the MTT assay, while antimetastatic potential was evaluated through the scratch assay. Apoptosis and cell cycle arrest were analyzed by flow cytometry. IC_50 data were analyzed using one-way ANOVA, and post hoc testing was performed using Tukey’s multiple-comparison test. Antiproliferation and scratch assay data were analyzed using two-way ANOVA followed by the Bonferroni test. Apoptosis and cell cycle assay data were analyzed using one-way ANOVA followed by the Tukey post hoc test. Phytochemical profiling indicated the existence of fifteen chemicals in both turmeric rhizome and soursop leaf extracts. The candidate combination ratio of turmeric rhizome to soursop leaf extracts was 1:21, exhibiting cytotoxic activity with an IC50 value of 32.2 ± 2.5 ug/mL. The combined extract was associated with antiproliferative, anti-migratory, and pro-apoptotic responses and induced G2/M phase cell cycle arrest in T47D cells.